IBM REVITALISASI POSYANDU DESA TAMBAKREJO - Zainafree, Intan; Mardiana, Mardiana (Universitas Negeri Semarang, 2015)
Public Health Center in the village Tambahrejo held regularly every month but the longer the people who come on the wane , whereas neighborhood health center is a milestone controller nutrition and growth of children as well as early detection of disease . The purpose of devotion is 1 ) optimize Tambakrejo wide growth , 2 ) Improve the skills of a cadre of neighborhood health center on anthropometric measurements , maternal counseling to children , 3 ) The completion of the module and pocketbooks mother toddler and videos of neighborhood health center management , 4 ) Establishment of medicinal plant families ( TOGA ) , 5 ) Motivating toddler ‘s mother to come to the neighborhood health center . The approach taken in this devotion is a neighborhood health center and counseling training cadres in the village Tambakrejo toddler ‘s mother . The results achieved , among others , enhancing the knowledge and skills of a cadre of neighborhood health center , the formation of neighborhood health center organizational structure , modules and videos of neighborhood health center management and a handbook for mothers toddlers , and there TOGA .